Infusing cardamom for recreational beverage / Hannis Fadzillah Mohsin, Zolkapli Eshak and Ibtisam Abdul Wahab - Mohsin, Hannis Fadzillah; Eshak, Zolkapli; Abdul Wahab, Ibtisam (Universiti Teknologi MARA, Negeri Sembilan, 2023)
The cardamom is a spice locally known as “buah pelaga” (GlobinMed, 2022). It is commonly used in cooking and baking, particularly in Indian and Middle Eastern cuisines (Ashokkumar et al. 2019). The cardamom has a strong, pungent flavour and aroma, and adds a distinctive taste to both sweet and savoury dishes. It is also extensively used as the flavouring agent in dairy and commercial food industry. For examples, it is utilised in the preparation of sweets, milk and milk products (e.g., gulabjamun), bakery products, cakes, bread, rice and meat preparations, alcoholic and non-alcoholic beverages, frozen desserts, candies, puddings, condiments, relishes, gravies, etc. This spice is obtained from the seeds of the cardamom plant, botanically referred to the Elettaria species or Elettaria cardamomum (E. cardamomum). It is native to southern India and Sri Lanka. In addition to its culinary uses, the cardamom is also used in traditional medicine for various purposes, including as a digestive aid and for relief from respiratory problems (Gochev et al. 2012).